Meningkatkan Kompetensi Pedagogi dengan Model Lesson Study bagi Guru SD di Kabupaten Bone - sudirman sudirman (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This study aims to improve pedagogical competencies especially elementary school teachers in Bone Regency. The study was conducted with a semi-experimental approach with the Lesson Study (LS) model. There were 20 teachers were directly involved from four elementary schools in Watampone. The procedures adopted were motivating, explaining, discussing, designing learning, implementing and observing learning, reflecting, designing and re-implementing the results of reflection in collaboration. After taking meet for three times, the results were very satisfying. Participants who stated LS were very appropriate to improve teacher pedagogical competence by 85%, exactly 15%, inaccurate and incorrect in each 0%. Qualitatively, the LS model is very effective in increasing the pedagogical competence of elementary school teachers in Bone. The main value of the LS model is that learning quality improvement was carried out directly in the learning process and activities. So, the teacher learns in the learning process about how to teach effectively and efficiently. It was recommended to teachers that this LS becomes one of the regular professional activities to improve the quality of the teaching profession.